Pectin extraction and analysis from blueberry (Vaccinium corymbosum L.) cv. O'Neall - Loyola López, Nelson; Núñez Mella, Patricia; Acuña Carrasco, Carlos (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The blueberries (Vacinium corymbosum) are a demand fruit because of their nutritional properties, low energetic value and high antioxidant content. Fruit non export characteristics are sent to the local industry for make juice, jelly and also were potential raw materials to obtain pectin. The present research had the following objectives: To measure the influence of the pH 2.0; 2.75 as well as the natural pH of the fruit (3.36) and the time and the temperature between 60 and 90 minutes at 90°C, and their influence over the extraction of blueberries pectin by acid hydrolisis; To measure the quality of the pectin, since sensory point of view, according to the sterification; To make and measure the gels from the pectin obtained at 35°, 50° and 65°Brix. The higher amount of pectin was obtained at pH 2.0 with 90 minutes and 3.22 g that included 0.93% (p/p). The degree of sterification was not over the 50% in all the treatments, so the pectin were classificate as "bajo metoxilo". The gel obtained at 50°Brix had a high level of acceptance for the panellists and they were classificate as "me gusta levemente" In relation to with the sensory attribute color, It was evaluated by the panellists such as "pálido" because of the light color of the pectin wich were used.